FOXTAIL MILLET (JEWAWUT) BLACK NOODLE WITH SUBTITUTION OF FOXTAIL MILLET FLOUR AND CHARCOAL (ACTIVE BAMBOO CHARCOAL POWDER) AS HEALTHY BLACK YAMIE DIVERSIFICATION - Wika Rinawati, Candra Dewi Kumalajati (Prosiding Pendidikan Teknik Boga Busana, 2020)
Foxtail millet or Otek (Pennisetum spp.) includes nutritious cereal plants. One effort that can be done is to innovate noodle products using substitute millet flour. Foxtail millet Black Noodle: black noodles with substitute for millet flour and charcoal (active bamboo charcoal powder) as a diversified healthy noodle substitute for millet flour is an innovative product that will discuss using local ingredients of millet. This study aims to obtain information on the nutritional value, formulation and acceptability of the best society for noodles with substitute for millet flour. The research model used is the R & D, namely the 4D Model which consists of four stages, namely: define, design, develop, and disseminate. Carried out through 3 stages: making millet flour; noodle making, testing of nutrient content and acceptance test. The proximate test results of black millet noodles have a total calorie count of 172 kal / 100g, 6.38% fat, 6.68% protein, 4.15% crude fiber, and 22.28% carbohydrate. The results showed that the best noodles were in the form of 35% millet flour. Keywords: jewawut, foxtail millet, Pennisetum spp., black noodles bamboo charcoal